Corpo-território e resistência: estratégias de uma mulher indígena citadina na educação - Cabral, Jhanine Magalhães (Brasil, 2025)
This study examines the coping strategies employed by an urban Indigenous woman in her educational journey, focusing on the intersectionalities shaping her trajectory. Its objective is to analyze how an urban Indigenous woman faced challenges and created possibilities for identity affirmation within the educational context. Drawing on the narrative of Ibiacy, a young Tikuna university student who is bilingual and from the Amazon region, the research highlights the social, cultural, and historical challenges faced by Indigenous women in urban settings. These challenges include discrimination, institutional precariousness, and tensions stemming from deterritorialization, which affect their right to education and their ability to remain in public universities. The analysis is grounded in the concept of body-territory, which links identity, ancestry, and territory to the resistance against multiple forms of structural violence that lead to psychological distress. Ibiacy and her mother represent the experiences of migrant Indigenous women who reconcile the value of their roots with urban spaces, reinterpreting their life experiences.